Pemanfaatan Media Sosial TikTok sebagai Media Promosi untuk Pengenalan Industri Kuliner di Yogyakarta melalui Akun TikTok @makanandiyogya - Harish Maulana Putra; Choirul Fajri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The pandemic period has ended, but many culinary business actors and umkm actors who still have not risen from the downturn during the Covid-19 pandemic in Yogyakarta. Efforts that can be made by umkm players and culinary entrepreneurs are marketing products and introducing their products through social media. Based on this, Tiktok social media has the potential as an efficient promotional media on how to market umkm products in the Special Region of Yogyakarta. Here is one Tiktok account that has content as a promotional media is the @makanandiyogya account. The methodology used is the constructivist paradigm which has the aim of gaining understanding, reconstructing qualitative research so as to get deep understanding result from individuals and the public. Tiktok is a short marketing media and Indonesia is the largest user of the Tiktok application, this application is easy able to hit trend developments, influenced by celebrities, Tiktok is also an interesting form of promotional marketing.